The Role of Extracurricular Activities in Developing Students' Soft Skills - Moh. Miftachul Choiri; sahri (International Journal of Education and Learning, 2026)
The main issue highlighted in this study is the suboptimal management and implementation of extracurricular activities in schools, resulting in the underutilization of their potential to develop students' soft skills. This study investigates the role of extracurricular activities in developing students’ soft skills, which are increasingly recognized as essential competencies for success in the 21st century. Grounded in the understanding that formal education often emphasizes cognitive learning while overlooking interpersonal and intrapersonal competencies, this research explores how extracurricular programs provide meaningful opportunities for holistic development. Using a qualitative case study approach, data were collected through in-depth interviews, observations, and documentation involving teachers, students, and school administrators. The analysis employed Miles and Huberman’s interactive model, covering data reduction, data display, and conclusion drawing. The findings reveal three major insights: first, extracurricular activities act as dynamic platforms for cultivating soft skills such as leadership, teamwork, communication, creativity, and resilience. Second, the implementation of these programs faces significant challenges, including limited resources, imbalanced participation, lack of professional training for facilitators, and time management constraints. Third, the success of extracurricular activities is strongly influenced by the active involvement of schools, teachers, parents, and communities, highlighting the importance of collaboration and strategic integration with real-life social issues. In conclusion, extracurricular activities are not merely complementary but serve as transformative tools for preparing students to face complex demands in academic, professional, and societal domains. The study recommends strengthening institutional support, enhancing teachers’ capacity, and fostering school–community partnerships to maximize the impact of extracurricular activities. By doing so, schools can ensure that students emerge as competent, empathetic, and future-ready individuals.